Membranous expression of podocalyxin-like protein is an independent factor of poor prognosis in urothelial bladder cancer - Boman, K (Nature Publishing Group, 2013)
BACKGROUND: Membranous expression of the anti-adhesive glycoprotein podocalyxin-like (PODXL) has previously been found to correlate with poor prognosis in several major cancer forms. Here we examined the prognostic impact of PODXL expression in urothelial bladder cancer. METHODS: Immunohistochemical PODXL expression was examined in tissue microarrays with tumours from two independent cohorts of patients with urothelial bladder cancer: n=100 (Cohort I) and n=343 (Cohort II). The impact of PODXL expression on disease-specific survival (DSS; Cohort II), 5-year overall survival (OS; both cohorts) and 2-year progression-free survival (PFS; Cohort II) was assessed. RESULTS: Membranous PODXL expression was significantly associated with more advanced tumour (T) stage and high-grade tumours in both cohorts, and a significantly reduced 5-year OS (unadjusted HR=2.25 in Cohort I and 3.10 in Cohort II, adjusted HR=2.05 in Cohort I and 2.18 in Cohort II) and DSS (unadjusted HR=4.36, adjusted HR=2.70). In patients with Ta and T1 tumours, membranous PODXL expression was an independent predictor of a reduced 2-year PFS (unadjusted HR=6.19, adjusted HR=4.60) and DSS (unadjusted HR=8.34, adjusted HR=7.16). CONCLUSION: Membranous PODXL expression is an independent risk factor for progressive disease and death in patients with urothelial bladder cancer.